2011
DOI: 10.1152/ajprenal.00243.2011
|View full text |Cite
|
Sign up to set email alerts
|

Tolvaptan inhibits ERK-dependent cell proliferation, Clsecretion, and in vitro cyst growth of human ADPKD cells stimulated by vasopressin

Abstract: Reif GA, Yamaguchi T, Nivens E, Fujiki H, Pinto CS, Wallace DP. Tolvaptan inhibits ERK-dependent cell proliferation, Cl Ϫ secretion, and in vitro cyst growth of human ADPKD cells stimulated by vasopressin. Am J Physiol Renal Physiol 301: F1005-F1013, 2011. First published August 3, 2011 doi:10.1152/ajprenal.00243.2011In autosomal dominant polycystic kidney disease (ADPKD), arginine vasopressin (AVP) accelerates cyst growth by stimulating cAMP-dependent ERK activity and epithelial cell proliferation and by pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
132
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(138 citation statements)
references
References 49 publications
4
132
0
2
Order By: Relevance
“…The effect on kidney volume in the first year was likely due to deflation caused by slowing fluid secretion, while the effect during the second and third years was likely due to decreased cell proliferation as secretion is maintained at a reduced level. This is supported by studies in cultured ADPKD cystic cells in which low concentrations of tolvaptan inhibited arginine vasopressinstimulated, chloride-driven fluid secretion and cell proliferation (24) and by clinical studies that demonstrated acute decreases in TKV as early as 1 and 3 weeks of treatment, which are probably not to be explained by effects on cell proliferation (17,25).…”
Section: Discussionmentioning
confidence: 82%
“…The effect on kidney volume in the first year was likely due to deflation caused by slowing fluid secretion, while the effect during the second and third years was likely due to decreased cell proliferation as secretion is maintained at a reduced level. This is supported by studies in cultured ADPKD cystic cells in which low concentrations of tolvaptan inhibited arginine vasopressinstimulated, chloride-driven fluid secretion and cell proliferation (24) and by clinical studies that demonstrated acute decreases in TKV as early as 1 and 3 weeks of treatment, which are probably not to be explained by effects on cell proliferation (17,25).…”
Section: Discussionmentioning
confidence: 82%
“…138 Tolvaptan also inhibits vasopressin-induced cell proliferation, chloride secretion, and in vitro cyst growth of human ADPKD cells. 139 …”
Section: V2 Receptor Antagonists: Rationale and Preclinical Trialsmentioning
confidence: 99%
“…4 Vasopressin promotes kidney-cyst cell proliferation and fluid secretion by means of up-regulation of adenosine-3′,5′-cyclic monophosphate (cAMP). 5,6 The suppression of vasopressin production, release, or action by means of hydration, 7,8 V 2 -receptor blockade, [9][10][11][12][13][14] or genetic mutation 15 has been shown to reduce cyst burden, protect kidney function, and prolong survival in rodent models.…”
mentioning
confidence: 99%